POLY ORGANIC POLYMER (3-HEXYLTHIOPHENE) P3HT as LIGHT SENSITIVITY in PROTOTYPE DYE-SENSITIZED SOLAR CELLS (DSSC) - Darmawan, Muh Iman; Cari, Cari; Supriyanto, Agus; Putra, Hadian Mandala; Fathurrahman, Fathurrahman (Universitas Mataram, 2021)
This research aims to review the characteristic of the nature of electricity polymer material poly(3-hexylthiophene) P3HT against increasing efficiency solar cells based on dye-sensitized solar cells (DSSC). The testing sample has done electricity P3HT el-kahfi 100/ I-V meter. The optical properties use spectrophotometer UV visible 1601 PC and characterizing IV DSSC use Keithley 2600 a type. The absorbance of P3HT polymer 1% has an absorption peak in the wavelength range of 300-650 nm. Thus the P3HT polymer material can absorb light in the visible wavelength range. The electrical properties of P3HT 1% indicate that the material has a response to light. In bright conditions, P3HT 1% shows a conductivity of 3.7x10-3Î©-1m-1 and in dark conditions 2.2x10-3Î©-1m-1. Meanwhile, Pt (Hexacloroplatinic IV) Platina as the opposing electrode can improve the performance of DSSC, which is because Pt (Hexacloroplatinic IV) functions as a catalyst to accelerate the redox reaction with electrolytes. The use of P3HT 1% can improve DSSC performance. DSSC using 1% P3HT and using Pt (Hexacloroplatinic IV) as the opposing electrode produced an efficiency value of 1.8x10-2%.